Pembelajaran Matematika Realistik Berbasis Etnomatematika terhadap Kemampuan Representasi Matematis pada Materi Geometri Kelas VII MTs Negeri 02 Bengkulu Utara - Nabila Isnaini; Asmara Yumarni; Poni Saltifa (Yayasan Darussalam Bengkulu, 2025)
The purpose of this study was to determine whether realistic mathematics learning based on ethnomathematics on geometry material could improve the mathematical representation ability of seventh grade students at MTs Negeri 2 Bengkulu Utara. The benefit of this study was to motivate students in mathematics learning so that it could. improve students' representation ability. This type of research is a quantitative quasi experimental design with a research approach. Data collection techniques were carried out with essay tests (pretest and posttest) and documentation. Data collection tools were in the form of essay questions. The results of the students' mathematical representation ability test obtained an N-Gain score of 0.687 <0.7, so the distribution of N-Gain scores was included in the moderate category and the interpretation of the effectiveness of N-Gain scores of 68.70 <70, so it was included in the quite effective category. Based on the results of the Independent Sample T-Test, the results were 0.01 (sig, 2-tailed), and this value was smaller than the significance level of 0.05. So the hypothesis proposed Ho is rejected and Ha is accepted, so that the increase in students' mathematical representation abilities with the realistic mathematics method based on ethnomathematics is better than students who learn with ordinary learning, and it can be concluded that realistic mathematics learning based on ethnomathematics is effective to be applied in the learning process.